Macro fundamental analysis on profit management as an intervening variable on financial performance - Yasin, Muhammad; Andjarwati, Tri (Bahasa Indonesia, 2024)
The study aims to determine the impact of macro fundamental on financial performance with profit management as the intervening variable on the plastic and packing sub companies registered in Indonesia Stock Exchange. The population in this study is the plastic and packing sub-sector companies listed in the Indonesian Stock Exchange in 2016-2020. The source of financial report data from the Indonesia Stock Exchange through the www.idx.co.id website and financial statements from the official website of each company in the plastic and packaging sub-sector has been published. The population of this study is 15 companies and purposive sampling is carried out for sampling so that 10 company samples are obtained. Research methods aided by Partial Least Square programs used with SmartPLS 3.0 software. The result of the study, shows that the macro fundamental against financial performance show have positive impact no significant, macro fundamentals against profit management has positive impact significant and profit management against financial performance have negative impact no significant.